Wuling San protects kidney dysfunction by inhibiting renal TLR4/MyD88 signaling and NLRP3 inflammasome activation in high fructose-induced hyperuricemic mice. (1st July 2015) - Yang, Ying; Zhang, Dong-Mei; Liu, Jia-Hui; Hu, Lin-Shui; Xue, Qiao-Chu; Ding, Xiao-Qin; Kong, Ling-Dong
Abstract: Ethnopharmacological relevance: Wuling San, a famous prescription in Chinese medicine, is composed of Polyporus, Poria, Alismatis rhizoma, Cinnamomi cortex and Atractylodis macrocephalae rhizoma, and promotes kidney function and diuresis. The main purpose of this study was to investigate its renal protective effect in high fructose-induced hyperuricemic mice. Materials and methods: ICR mice were fed with 30% fructose in drinking water for 6 weeks to induce hyperuricemia and renal dysfunction. Then mice were orally administrated for other 6 weeks with Wuling San (987, 1316, 1755 and 2340 mg/kg), allopurinol (5 mg/kg) and water daily, respectively. Serum and urine levels of uric acid, creatinine and blood urea nitrogen (BUN) were measured. Hematoxylin and eosin staining was used to assess renal histological changes. Renal interleukin (IL)-1β concentrations were measured using ELISA kit. Renal protein levels of organic ion transporters, as well as toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88) signaling and pyrin domain containing 3 (NLRP3) inflammasome were determined by Western blot assay. Results: Wuling San significantly decreased serum uric acid, creatinine and BUN levels, increased fractional excretion of uric acid (FEUA ) in fructose-fed mice. It restored fructose-induced dysregulation of renal urate transporter 1 (URAT1), glucose transporter 9 (GLUT9), ATP-binding cassette subfamily G member 2 (ABCG2) and organic anion transporter 1 (OAT1), as well as organic cation transporter 1 (OCT1) and OCT2 in mice. Wuling San obviously alleviated infiltration of inflammation cells in kidney glomerulus of fructose-fed mice. Moreover, Wuling San suppressed the activation of TLR4/ MyD88 signaling to inhibit nuclear factor κB (NF-κB) signaling and mitogen-activated protein kinases (MAPKs) activation in fructose-fed mice. Additionally, Wuling San decreased NLRP3 inflammasome activation and IL-1β secretion in the kidney of fructose-fed mice. Conclusion: Wuling San exerts renal protective effect by modulating renal organic ion transporters in fructose-induced hyperuricemic mice. The molecular mechanism of its action may be associated with the suppression of TLR4/MyD88 signaling and NLRP3 inflammasome activation to reduce IL-1β production in high fructose-induced hyperuricemic mice. Graphical abstract: